Актуальні проблеми протидії корупції - Дем’янчук, Юрій Вікторович; Демьянчук, Юрий Викторович; Dem'janchuk, Jurij (Одеса : Юрид. л-ра, 2014)
The article analyzes the causes and problems of combating corruption in the public service, the level of corruption and its impact on the socio-political, social and economic development of Ukraine.
Дем'янчук Ю. В. Актуальні проблеми протидії корупції / Ю. В. Дем'янчук // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 347-353.
Keywords: державна служба; корупційна діяльність; корупція; протидія корупції; запобігання корупції; государственная служба; коррупционная деятельность; коррупция; противодействие коррупции; предотвращение коррупции; public service; corrupt activities; corruption; anti-corruption; preventing corruption